Antioxidant evaluation-guided chemical profiling and structure-activity analysis of leaf extracts from five trees in Broussonetia and Morus (Moraceae) - Cao, Xinxin; Yang, Lingguang; Xue, Qiang; Yao, Fan; Sun, Jing; Yang, Fuyu; Liu, Yujun (Scientific reports, 2020)
Morus and Broussonetia trees are widely used as food and/or feed. Among 23 phenolics identified from leaves of five Moraceae species using UPLC–QTOF–MS/MS, 15 were screened using DPPH/ABTS-guided HPLCs, including seven weak (flavonoids with one hydroxyl on B-ring) and eight strong (four caffeoylquinic acids and four flavonoids, each with a double hydroxyl on B-ring) antioxidants. We then determined the activity and synergistic effects of individual antioxidants and a mixture of the eight strongest antioxidants using DPPH-guided HPLC. Our findings revealed that (1) flavonoid glucuronide may have a more negative effect on antioxidant activity than glucoside, and (2) other compounds in the mixture may exert a negative synergistic effect on antioxidant activity of the four flavonoids with B-ring double hydroxyls but not the four caffeoylquinic acids. In conclusion, the eight phenolics with the strongest antioxidant ability reliably represented the bioactivity of the five extracts examined in this study. Moreover, the Morus alba hybrid had more phenolic biosynthesis machinery than its cross-parent M. alba , whereas the Broussonetia papyrifera hybrid had significantly less phenolic machinery than B. papyrifera . This difference is probably the main reason for livestock preference for the hybrid of B. papyrifera over B. papyrifera in feed.